Assessment of red blood cells morphology and the associated factors among young Chinese students pursuing tertiary education - Khoo, Sin Ye (2023)
Smoking cigarette, vaping, secondary smoker and exercise are several factors that can alter the morphology of the RBC and other blood parameters. Therefore, the main objective of this study was to determine the prevalence of abnormal red blood cells among the young adults and to analyse the associated factors of abnormal red blood cells among the young adults. This study conducted using a cross-sectional survey, using the Google Form questionnaire that was developed. The sampling was started from November 2022 to February 2023, and successful recruited 321 participants in this study. In the clinical assessment, anthropometry measurement, hemoglobin level, blood smearing and blood staining were performed. The microscopic view was conducted to identify the blood morphology abnormalities. Chi-square test was performed to analyse the association between the blood morphology abnormalities with the sociodemographic characteristics, exercise, smoking status, anthropometry measurement and hemoglobin level. The result showed the majority of the iii students possessed RBC with smaller and paler in colour than normal. The prevalence of anisocytosis, hypochromic and poikilocytosis are 50.8%, 53.3% and 47.0% respectively among the young adults. Significant associations were discovered between the gender, secondary smokers, height and weight. The variation in RBC colour was found to be significantly affected by gender (ꭓ2=6.576, p=0.010), height (ꭓ2=21.040, p=0.000) and weight (ꭓ2=13.310, p=0.038). In addition, only secondary smokers (ꭓ2= 7.182, p=0.028) was found to have a significant influence on variation in RBC size. In conclusion, even the participant recruited was healthy, but there were several types of blood abnormalities can be observed from the blood due to some unhealthy lifestyle. Therefore, proper education should be tailored to the young adults in order to raise the awareness of seriousness of smoking that affect the red blood cells morphology as an early underlying symptom for latter diagnosis of chronic disorders